PUNCHLINE TWEETS: NEGOTIATING RELIGIOUS MODERATION ON INDONESIAN SOCIAL MEDIA - Thohir, Muhammad; Dimyathi, Muhammad Afifudin (Khazanah: Jurnal Studi Islam dan Humaniora, 2024)
When a statement enters the public domain such as social media, it will have many implications for the discourse and critical context that accompany it. Likewise, with debates on social media Twitter that intersect with religious understanding such as radicalism, there are funny line accounts present that try to break the high tension of cyber warfare. This study aims to describe how Twitter accounts openly negotiate the educational values ​​of religious moderation on social media. By using a web-based social phenomenology approach, this study uses a qualitative descriptive method. Twitter account @NUgarislucu was chosen as the data source and data was collected through online documentation. While the analysis uses critical discourse analysis from Teun A. van. Dijk. The results reveal that punchline tweets have been used to negotiate educational values ​​of religious moderation through the integrated priciples of tawassuth, tasâmuh, and tawâzun. Negotiations were carried out with various themes, including (1) religious conversion, (2) religion and suicide bombings, (3) religion and political identity, (4) religion and the political order of the khilāfah., and (5) religion and nationalism. Thus, the findings reinforce the notion that the delivery of religious content which is often considered heavy and boring is more acceptable to netizens through humor.